The Conservation of Murals – A New Trend in Protecting Works of Art - Sawicki, Tytus (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2022)
In recent years, a trend has emerged in the field of art conservation, the aim of which is to protect street art objects. Attempts to conserve murals face many problems. This is due to various factors – lack of time distance to this type of objects, difficulties in assessing their artistic value, frequent lack of interest of artists in the conservation of their works, material impermanence of murals, their often-occasional nature; also, the fact that most of these objects are not legally protected. The paper discusses the problems faced by an art restorer who wants to save murals. Examples of murals are presented, the conservation of which is not possible, among others, due to the fact that the houses on which they were painted are intended for demolition. There are also examples of murals whose rescue from destruction gained public approval and the conservation of which was carried out. The paintings are in a very poor condition. This is a feature of most murals, which are usually made on old, unrepaired plasters with low-quality paints. Their maintenance is a very difficult task. The presentation shows the various stages of conservation of works lacated in Warsow. The conservation of the murals is carried out in order to preserve street art facilities. Apart from the involvement of art conservators, social support for this type of activity is also important. However, one should be aware that most of murals have no chance of becoming a permanent part of the city landscape. Their fate will be determined by chance.